A numerical study on the pendant superheater of a 1000 MW coal-fired supercritical CO2 boiler. (5th February 2021) - Chen, Tang; Su, Hong-liang; Sun, Qiang
Graphical abstract: Highlights: Two high temperature cores of gas emerge at the furnace outlet. Radiation and convective energy flux has a high value region near central rear wall. Outlet temperature for S-CO2 presents one peak in X-direction. Tube inlet temperature drop/rise signal is smoothed by the system. Abstract: This work focuses on the pendant superheater (PSH) of a 1000 MW coal-fired supercritical CO2 (S-CO2) boiler. Three-dimensional simulation of coal combustion is performed, in order to obtain the heat load distribution on the S-CO2 fluid. The tube lines simplified from the real system are constructed in CAD software. The results show that two high temperature cores of gas emerge at the furnace outlet, which is also two cores of low convective energy flux. The two high temperature cores are dramatically cooled down by the PSH. As a result, the S-CO2 in the central region near the rear wall absorbs more energy. The final heating effect is that the outlet temperature for S-CO2 only has one peak rather than two in X-direction.